2012
DOI: 10.1017/s0021932012000041
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Association Between Maternal Education and Use of Health Services in Ghana: Exploring the Role of Health Knowledge

Abstract: SummaryThis paper examines the role of health knowledge in the association between mothers' education and use of maternal and child health services in Ghana. The study uses data from a nationally representative sample of female respondents to the 2008 Ghana Demographic and Health Survey. Ordered probit regression models evaluate whether women's health knowledge helps to explain use of three specific maternal and child health services: antenatal care, giving birth with the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 42 publications
17
58
1
1
Order By: Relevance
“…Women in our study exhibited low health literacy for interpreting and operationalizing ANC education even though more than half of the women completed primary education. Our qualitative findings support a recent quantitative study that examined the relationship among maternal education, health knowledge, and use of health services in Ghana (Greenaway, Leon, & Baker, ). Greenaway et al () showed that more years of maternal education increased women's understanding of health, and this comprehension of health led to increased use of maternal and child health services.…”
Section: Discussionsupporting
confidence: 85%
“…Women in our study exhibited low health literacy for interpreting and operationalizing ANC education even though more than half of the women completed primary education. Our qualitative findings support a recent quantitative study that examined the relationship among maternal education, health knowledge, and use of health services in Ghana (Greenaway, Leon, & Baker, ). Greenaway et al () showed that more years of maternal education increased women's understanding of health, and this comprehension of health led to increased use of maternal and child health services.…”
Section: Discussionsupporting
confidence: 85%
“…Mass media exposure (that ideally conveys some rudimentary information on health and health care) positively affects the use of reproductive health services among women in Bangladesh in the context of intimate partner violence [41]. In contrast, however, Greenaway and colleagues [76] showed that in Ghana, indicators for women’s access to mass media and media exposure were not associated with use of services.…”
Section: Resultsmentioning
confidence: 99%
“…This fact was studied in Ghana revealed that mothers' duration of school education is strongly associated with health literacy 8 . The findings of another study done in Bangladesh showed that a low level of education on cholera among risky groups calls for supporting health education activities to increase their knowledge on cholera 9 , another study done on the old people in China revealed that candidates who finished high school or higher had 6, 4, and 3 times bigger odds of possessing adequate health literacy than those who .…”
Section: Discussionmentioning
confidence: 99%